Extraskeletal Ewing sarcoma of the anterior abdominal wall - Raza, Mohammad Ibrahim; Raza, Mohammad Habib; Varshney, Lakshya; Abhinava, Kolari (Indian Journal of Case Reports, 2024)
Extraskeletal Ewing sarcoma (EES) is a relatively rare primary tumor of the soft tissues, it accounts for 20–30% of all reported cases of EES which is a neoplasm that usually occurs in children and young adults and presents as an undifferentiated primary bone tumor. Infrequently, this tumor can have an extraskeletal origin, known as EES. We report a case of Ewing’s tumor involving the anterior abdominal wall without any associated skeletal location. The clinical examination suggested a benign neoplasm arising from the subcutaneous tissue. However, ultrasound, magnetic resonance imaging, and fine-needle aspiration that were done preoperatively suggested a malignant neoplasm. No evidence of metastasis was present. The diagnosis of EES was confirmed after surgical excision. Histopathological and immunohistochemical examinations were helpful in the confirmation of the diagnosis. The patient had an uneventful post-operative recovery. He was started on chemotherapy and is on regular follow-up.